Deskový most v Újezdu u Brna - Dočkal, Miloš (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Předmětem bakalářské práce je navrhnout mostní konstrukci v Újezdu u Brna. Most je součástí místní komunikace a slouží k převedení dopravy přes řeku Litavu. Mostní konstrukce je navržena ve dvou variantách. Vybraná varianta je předpjatá betonová deska o délce 19,8 metrů a šířce 5,6 metrů. Výpočet zatížení je řešen v programu Scia Engineer 2012 a hodnoty jsou ověřeny ručním výpočtem. Konstrukce je posuzována ručně podle Eurokódu.

The subject of bachelor´s thesis is to design a bridge construction in Újezd u Brna. The bridge is part of a local road and it is used to transfer across the river Litava. The bridge construction is designed in two variants. The chosen variant is prestressed concrete construction with a lenght of 19,8 metres and a width of 5,6 metres. The calculation of loads is deal with software Scia Engineer 2012 and the results are verified with manual calculation. The construction is manual-calculated according to Eurocode.
Slab bridge in Újezd at Brno
Keywords: Deskový most; mostní konstrukce; předpjatá betonová deska; posouzení; ztráty předpětí; monolitická deska; Slab bridge; bridge construction; prestressed concrete construction; design; losses of prestressing; monolithic construction